Estudo não clínico do perfil psicofarmacológico do álcool cinâmico - Andrade, Humberto Hugo Nunes de (2019)
Cinnamic alcohol (AC) is a phenylpropanoid found found in the essential oil of cinnamon bark. AC analogs have effect in the Central Nervous System already reported in the literature, however there are no reports of studies of the pharmacological activity of cinnamic alcohol. In the behavioral pharmacological screening, the different doses tested by the intraperitoneal route (12.5, 25, 50, 100 and 200mg / kg) presented psychodepressive behavioral alterations, such as decreased ambulation, ptosis eyelid analgesia and loss of atrial reflex. No deaths were observed. LD50 was estimated to be approximately 500 mg / kg, following the protocol of OECD 432. In the subsequent experiments, doses of 12.5, 25, 50, 100 and 200 mg / kg (i.p.) were listed. In the open field test it was verified that the AC presents a psychodepressive drug profile, because there was a significant decrease in parameters such as ambulation and rearing of the animals. Through the rota-rod test, it was possible to verify that the animals treated with AC had no alterations in motor coordination, ruling out a possible neurotoxic or myorelaxant effect. In order to evaluate the anxiolytic activity, the high labyrinth test did not show significant changes in the length of stay in the open arms, showing a non-anxiolytic AC activity. In the forced swimming test, CA increased the immobility time of the mice submitted to the protocol, reinforcing the depressor effect, presented in the preliminary tests. In the formalin test there was a decrease in the licking time in the two phases, evidencing that CA promotes central antinociception.